Combating Obesity With Thermogenic Fat: Current Challenges and Advancements - Pan, Ruping; Zhu, Xiaohua; Maretich, Pema; Chen, Yong (Frontiers in Endocrinology, 2020)
Brown fat as well as beige fat which arises in white fat in the process of “browning” have been 13 identified to contribute to the non-shivering thermogenesis in mammals in response to cold 14 stimulation. Targeting these fat become feasible to combat obesity. Currently, anti-obesity 15 medications have been applied to mostly act as selective 3-adrenergic receptor (AR) agonists, 16 since the -AR signaling plays a crucial role in cold-induced thermogenesis. However, it is 17 accompanied by side effects such as a high blood pressure, which may in turn cause cardiovascular 18 disease. Although other targets are under investigation, such as previous identification of other 19 kinds of beige adipocyte which can be activated independently of the AR signaling, they still need 20 to be confronted with strict verification in prior to any clinical trial. In this review, we focus on 21 discussing the challenges for targeting brown/beige fat thermogenesis to combat obesity